Simulação atomística das manganitas h-RMnO3 (R = Er, Tm, Yb, Lu, In e Sc) puras e dopadas com metais de transição e terras raras - Sousa, Afrânio Manoel de (2018)
In this work, we studied the h-RMnO3 (R = Er, Tm, Yb, Lu, In and Sc) manganites which are materials with important multiferroic properties. The classical atomistic simulation was used in order to obtain a set of interatomic potentials that describe the structural properties of manganite family in ferroelectric phase (FE). The structural properties such as the lattice parameters, the unit cell volume and the interatomic distances were investigated and compared with results of the literature. The influence of chemical pressure on the structural properties of these compounds was analyzed. It was observed that the lattice parameters (a and c) and the volume of the unit cell increase as the ionic radius of the R3+ ion increases. All h-RMnO3 manganites were studied under hydrostatic pressure up to 40 GPa. It was observed that the lattice parameters (a and c) and the unit cell volume decrease with an increase in the hydrostatic pressure. The paraelectric phase (PE) was studied using the interatomic potential developed in the ferroelectric phase. Thus, the structural properties in this phase were obtained and compared with the literature. Effects of doping of trivalent ions on the h-LuMnO3 manganite were studied in three crystallographic sites (Mn, Lu1 and Lu2). Solution energy was calculated for all dopants (Al, Cr, Ga, Fe, Sc, Yb, Er, Y, Ho, Gd, Eu, Sm, Nd e La) and the results showed that the Mn site has the lowest solution energy, therefore, the Mn site is energetically more favorable. The metals (Al, Cr, Ga, Fe) dopants proved to be more favorable to incorporate at the Mn site than rare earths ones (Sc, Yb, Er, Y, Ho, Gd, Eu, Sm, Nd and La), but at the Lu site the rare earths are energetically more favorable to incorporate. The calculated interatomic distances at the Mn site decreases when doping with metal (Al, Cr, Ga and Fe). However, these distances increase when doping is done with rare earth (Sc, Yb, Er, Y, Ho, Gd, Eu, Sm, Nd and La). In addition, important ferroelectric distortion properties were evaluated due the change in the tilting angle of the MnO5 bipyramid. The tilting angle increases in the pure system if the doping is done with metals (Al, Cr, Ga, Fe) for all sites. On the other hand, the tilting angle decreases with rare earth ions incorporation at the Mn and Lu1 sites and increases in the rare earths doping at the Lu2 site.